Transfer of Tumor-Bearing Mice Intestinal Flora Can Ameliorate Cognition in Alzheimer's Disease Mice - Hang, Zhongci; Cai, Shanglin; Lei, Tong; Zhang, Xiaoshuang; Xiao, Zhuangzhuang; Wang, Donghui; Li, Yingxian; Bi, Wangyu; Yang, Yanjie; Deng, Shiwen; Wang, Li; Li, Quanhai; et al. (Journal of Alzheimer's disease, 2022)
Fecal microbiota transplant (FMT) is a potential treatment approach for many diseases. Alzheimer's disease (AD) and cancer have been proven to have a specific antagonistic relationship to FMT. This article aims to explore whether intestinal flora transplantation from cancer individuals can ameliorate cognitive impairment. Morris water maze and object recognition tests were performed to assess cognitive function after the fecal flora from tumor-bearing and WT mice were transplanted into AD mice by gavage. The effect of flora transplantation on AD was analyzed by thioflavin T staining, western blot, and 16S RNA sequencing. AD mice with FMT significantly improved short-term memory level and cognitive ability compared with Tg + NaCl group. Inflammatory factors in the plasma were regulated, and Aβ plaques burden in the hippocampus and cortex were decreased. FMT in the tumor-bearing group showed a higher significant amelioration in symptoms compared to the healthy group. 16S RNA sequencing revealed that FMT treatments could reverse the increased Firmicutes and Prevotella and the decreased Bacteroidetes, Bacteroides, and Sutterella in AD mice. AD mice transplanted with tumor-bearing mice feces additionally increased the density of Oscillospira, Odoribacter, and AF12. Furthermore, the predicted functional analyses showed that the metabolism of inorganic and organic salts in the intestinal flora of AD mice was also reversed by FMT. Intestinal flora transplantation from tumor-bearing mice can ameliorate the cognitive impairment of AD mice.